Linearity Trade-offs in High-Voltage RF Switches for Antenna Tuning Applications - Özdamar, Oguzhan; Weigel, Robert; Solomko, Valentyn; Hagelauer, Amelie (Asia-Pacific Microwave Conference Proceedings, APMC, 2020)
An analysis describing the harmonics distribution in a shunt aperture tuning RF switch operating in OFF mode is presented in the paper. The focus is put on the second and third harmonic power distribution as a function of geometry of an RF switch. The analytical findings are verified with measurements for which the two integrated circuits were manufactured in Infineon 130 nm RF switch technology. Both the analytical model and the measurements show, that there is a trade-off between the second and third harmonic depending on the geometry of the RF switch.
Created from Fastlane, Scopus look-up
Keywords: antenna tuning; aperture tuning; harmonics; high-voltage RF switch; IC design; nonlinearity